Um jus cogens inderrogável : direito humano ao meio ambiente saudável - Galvão, Silvano Macedo (2011)
This study aims at identifying the existence of environmental jus cogens, due to the fact that it is a norm accepted by the international community as non-derogable and capable of nullifying any other international norm that opposes it. For this reason, the human rights, their evolution, the characterization of the fundamental rights and the existence of the fundamental right to a healthy environment, implicit or explicitly, in the international norms and in the doctrine were analyzed. As a result of the human rights evolution, the international system for the protection of human rights and the position and protection of the International Courts in relation to environmental issues, even regarding individual protection were analyzed. This was to identify and verify the interconnection of the human rights with the right to the health environment for the protection of people’s life, health and well-being. To show the importance of the issue and the acceptance of the environmental protection by the states in their internal rights, the insertion of the right to the environment in its legal system and in the development of public policies with the emergence of the social environmental State was analyzed. This current situation of environmental protection in the international norms and in the internal rights of the States allowed the identification of the appearance of environmental jus cogens. Based on this reality the nonderogability of the norms of environmental protection from the principles of the prohibition of retrocession, prevention and precaution in the context of the risk society was studied. The consequences of the environmental protection in the context of multiculturalism as well as the need for a new ethic for the purpose of environmental protection were also analyzed. These propositions make it possible to verify the emergence of the environmental jus cogens in the international community that seeks for legal solutions to reestablish the safety of a future life, in the context of climatic changes and of the risk society, since most of the States members of the United Nations have the right to the environment in their internal rights and are part of the main treaties related to the international system of environmental protection. To confirm this evidence the discussion of the jus cogens in the International Courts that already protect environment even if through reflective way, to protect the right to life, to peace or to property. As a result, the jus cogens was analyzed as a source of the international right, differing it from the erga omnes duties, highlighting the patterns for its identification, since it derives from the fundamental human rights as a way of showing its non-derogability, even when facing another norm of the same status and regardless of any manifestation of the States that did not participate in its negotiation. Finally it is considered as a qualitative approach, because it privileges an interpretative treatment to the basic categories that are included in the objectives of the study, which is to identify the existence of an environmental jus cogens, its characterization and non-derogability.